The quartic analog to the RSA cryptosystem - Wong, Tze Jin; Md Said, Mohamad Rushdan; Mohd Atan, Kamel Ariffin; Ural, Bekbaev (Universiti Putra Malaysia Press, 2007)
This paper reports an investigation into a public key cryptosystem, which is derived from a forth order linear recurrence relation and is based on the Lucas function.This cryptosystem is also analogous to the RSA,LUC and LUC3 cryptosystem. The explicit fomulation involves a generalisation of the Euler Totient function, which underlie the algebra of the RSA cryptosystem.